Molecular and supramolecular properties of a Hg(II) complex with (E)-N, N′-bis(2-pyridyl)iminoisoindoline: synthesis, spectroscopy, X-ray structure and Hirshfeld surface analyses, and DFT calculations. Issue 6 (19th March 2017) - Bitzer, Rodrigo S.; Visentin, Lorenzo C.; Hörner, Manfredo; Nascimento, Marco A. C.; Filgueiras, Carlos A. L.
Abstract: A scarcity of metal complexes containing ( E )- N, N′ -bis(heteroaryl)iminoisoindolines has prompted us to investigate the coordinating ability and supramolecular behavior of ( E )- N, N′ -bis(2-pyridyl)iminoisoindoline (2-pyimiso), a versatile iminobis(pyridyl) ligand. The 1:1 reaction of HgCl2 with 2-pyimiso in MeOH afforded a dinuclear complex, [HgCl(2-pyimiso)2 (μ-Cl)2 ] (1 ). The complex has been characterized by elemental microanalysis, vibrational spectroscopy (FTIR and FT-Raman) and 1 H NMR spectroscopy. DFT calculations at the B3LYP-D3/LACV3P** level have been used in support of our vibrational analysis. Single-crystal X-ray diffraction data have shown that the coordination geometry of1 is intermediate between the trigonal pyramidal and seesaw shapes insofar as each Hg(II) is four-coordinate and 2-pyimiso is a monodentate ligand. X-ray structure and Hirshfeld surface analyses have revealed that the supramolecular arrangement of1 comprises perpendicular 1-D chains along the [011] direction assembled by nonclassical C–H⋯Cl–Hg and C–H⋯ π hydrogen bonds. Moreover, adjacent sheets parallel to the bc -plane are interconnected by C–H⋯Npy, π – π py stacking, and Hg⋯ π py interactions. Abstract :